Screening of blood donors for chronic Coxiella burnetii infection after large Q fever outbreaks. Issue 11 (12th June 2014) - Slot, Ed; Hogema, Boris M.; Molier, Michel; Zaaijer, Hans L.
<x xml:space="preserve">Abstract</x> Background The Netherlands experienced major Q fever outbreaks from 2007 through 2009. An increasing number of human chronic Q fever cases has been reported in the affected area. Blood donors unaware of chronic Coxiella burnetii infection might be infectious for transfusion recipients. Local blood donations were screened for serologic signs of chronic Coxiella infection. Study Design and Methods From August 2012 through January 2013, a total of 2490 serum samples were collected from all consenting blood donors in the most affected Q fever outbreak area and screened for Phase II anti‐Coxiella immunoglobulin G antibodies using an enzyme‐linked immunosorbent assay (ELISA). (Phase II antibodies are considered indicative for resolved or ongoing Coxiella infection.) Reactive samples were confirmed by quantitative immunofluorescent Phase I and II antibody testing. A Phase I antibody titer of at least 1024 was considered indicative for chronic Coxiella infection. For 179 donors archived samples from 2009 and 2010 were available to study the long‐term course of Coxiella antibodies. Results A total of 110 of 2490 donors were confirmed positive for Phase II Coxiella antibodies (4.4%; 95% confidence interval, 3.7%‐5.3%), of which 79 were reactive for Phase I antibodies, with a maximum titer of 256. In 15 of 24 donors (62.5%), testing positive for Phase II antibodies in 2009 and 2010, ELISA reactivity had declined to negativity in 2012 and 2013. Conclusion After large Q fever outbreaks in the Netherlands, no sign of potentially infectious chronic Coxiella infection was found among blood donors in the most affected area. Using an ELISA for detection, Coxiella antibodies in previously exposed donors waned quickly.